AN ERROR ANALYSIS ON THE USE OF ENGLISH ARTICLES IN STUDENTS’ WRITTEN DESCRIPTIVE TEXTS A Case of Class X MIA 1 of SMA N 1 Binangun, Cilacap in the Academic Year 2014/2015 (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2016)
This study is a case study which investigates errors on the use of English articles. It is focused on the errors made by tenth grade students of SMA N 1 Binangun, Cilacap in their written descriptive texts. The total of 32 students of class X MIA 1 became the subjects of this study and they were asked to write descriptive texts. The object of this study was errors in using English articles which occurred in their texts. The data were analyzed based on Ellis’s Error Analysis Procedure and normalization formula by Pica. The result of this study from the highest to the lowest exposed errors are: indefinite a/an-for-zero errors (61.51%), zero-for-indefinite a/an errors (22.19%), definite the-for-indefinite a/an substitution error (5%), definite the-for-zero substitution error (4.65%), zero-for-definite the substitution error (4.41%), and indefinite a/an-for-definite the substitution error (2.23%). Based on the result gained from this study, the dominant error exposed by the students is grammatical error (indefinite a/an-for-zero). This condition shows that the students find difficulties to differentiate between countable and non-countable nouns. It is suggested that the teacher give more attention to this problem and start to improve his attitude in teaching grammar.